PROTECTION LAW TO OWNER RIGHT TOP CREATION SONGS ARRANGED BY OTHER PARTIES AND RE-UPLOADED ON YOUTUBE WITHOUT THE PERMISSION OF THE COPYRIGHT OWNER - Simon Baitmetan; Ariyanti (Faculty of Law, Widya Gama University, Malang, 2026)
The legal protection of copyright plays an important role in safeguarding intellectual works, including songs that are arranged and re-uploaded on digital platforms such as YouTube without authorization. This research aims to analyze the forms of legal protection available to copyright owners and the legal steps that can be taken to prosecute infringers. The research uses a normative legal method with a normative juridical approach that focuses on analyzing regulations, legal literature, and related documents. The results show that Law No. 28 of 2014 on Copyright provides moral and economic protection automatically since the work is realized in real form. Based on Law Number 28 of 2014 concerning Copyright, the morals rights and economic rights of the creator are protected automatically since the work is realized in tangible form. Infringement reporting mechanisms such as copyright takedown on YouTube provide a quick solution for creators, while civil and criminal legal actions can provide a deterrent effect to violators. The importance of collaboration between creators, the government, and the Collective Management Institution (LMK) in managing royalties and copyright protection is also highlighted. The results of this research are expected to encourage wider legal awareness and create a sustainable creative ecosystem.